An analysis of the Slovenian terminology of musical forms - Mihelač, Lorena (Array, 2019)
The article presents the results of the analysis of the use of basic Slovenian music terms used in writing about musical structure. Since this terminology includes a large number of terms, we have decided to limit the analysis of basic terms to the following ones: tone, note, motif, figure, melody and musical form. For the purposes of research, we have created a one-language corpus on www.sketchengine.co.uk, which contains graduate, masters‘ and doctoral theses dealing with music analysis and several textbooks dealing with musical forms. Such a modern corpus approach makes it easier to search terms and their meanings, which ultimately leads to interesting results on how to use certain terms.